Pengaruh literasi ekonomi, e-commerce, lingkungan keluarga terhadap minat berwirausaha mahasiswa - Tiara Rahma Tanjung Sari; Waspodo Tjipto Subroto (Jurnal Riset Pendidikan Ekonomi, 2023)
Entrepreneurship is a field that should be taken into account as a driver of a country's economy. However in reality, entrepreneurial interest in students is still relatively low. This study was conducted with the aim of analysing the effect of economic literacy, e-commerce, and family environment on student entrepreneurial interest. The research method used is causal associative research with a quantitative approach. The population and sample in this study were Office Administration Education Study Program, Accounting Education Study, Economics Education, and Commerce Education 2019 batch of Surabaya State University with a total of 214 students. Data collection techniques through written tests and questionnaires were then analysed using the multiple linear regression analysis model of the IBM SPSS version 25 approach. The results showed that the variables of economic literacy, e-commerce, family environment have an influence on student entrepreneurial interest both partially and simultaneously. The results of these findings are expected to be input for the family, especially parents to create a harmonious family atmosphere and for the university, especially the department of economics FEB Surabaya State University to improve understanding of economic literacy and the provision of courses related to the concept of e-commerce, so that entrepreneurial interest in students can grow and also increase so that they become graduates who are not only competent in accordance with the field of study pursued but also have provisions as an entrepreneurial spirit.